2021
DOI: 10.1111/jcmm.16647
|View full text |Cite
|
Sign up to set email alerts
|

PAICS is related to glioma grade and can promote glioma growth and migration

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…As a key regulatory enzyme involved in the de novo purine biosynthesis pathway, PAICS serves an important role in regulating cell proliferation, growth, and apoptosis. PAICS promotes tumor cells proliferation and migration, whereas the knockdown of PAICS leads to tumor cell cycle arrest and apoptosis 30,39 . In this study, shRNA‐mediated PAICS knockdown showed significant suppression on the viability and proliferation, while induction on apoptosis of EGFR wild‐type NSCLC cells.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…As a key regulatory enzyme involved in the de novo purine biosynthesis pathway, PAICS serves an important role in regulating cell proliferation, growth, and apoptosis. PAICS promotes tumor cells proliferation and migration, whereas the knockdown of PAICS leads to tumor cell cycle arrest and apoptosis 30,39 . In this study, shRNA‐mediated PAICS knockdown showed significant suppression on the viability and proliferation, while induction on apoptosis of EGFR wild‐type NSCLC cells.…”
Section: Discussionmentioning
confidence: 54%
“…PAICS is overexpressed in glioma, breast cancer, pancreatic cancer, gastric cancer, prostate cancer, bladder cancer, and colorectal cancer, and its high expression is closely related to the poor survival of tumor patients. [29][30][31][32][33][34] However, a recent paper by Kobayashi et al 29 analyzed 1659 colorectal tumor samples demonstrated a reduction of PAICS due to genetic deletion of chromosome 4q during colorectal tumor progression and metastasis. Correspondingly, loss of PAICS is also correlated with poor relapse-free survival in stage III colorectal tumor patients.…”
Section: Discussionmentioning
confidence: 99%
“…One study has reported that PAICS can promote tumor proliferation and migration in neuroblastoma [32], though it has also been shown to play an important role in a variety of tumors [4][5][6]. Our previous study also found that PAICS plays an oncogene role in glioma [9]. Bioinformatics analysis indicated that SPI1 can bind to the PAICS promoter region.…”
Section: Discussionmentioning
confidence: 81%
“…Numerous studies demonstrated that PAICS can promote the proliferation and migration of many tumors [3][4][5][6][7][8]. Our previous study also found that PAICS plays an oncogene role in glioma [9]. In this project, we intend to further study the transcriptional regulation of SPI1 and PAICS through luciferase assay, gene transfection technology, Western blot and other techniques.…”
Section: Introductionmentioning
confidence: 97%
“…In fact, purine-metabolizing enzymes also participate in other biological processes. For instance, CD39 and ADA are involved in immune regulation [ 18 , 58 , 59 , 83 ]; IMPDH carries out the function of a transcription factor [ 282 ]; SAM Domain And HD Domain-Containing Protein-1 assists in regulating the cell cycle [ 283 ] and phosphoribosylaminoimidazole succinocarboxamide synthetase is correlated with DNA damage repair [ 284 , 285 ]. It can help to identify new interventions in tumor process if we focus on purine metabolic processes and understand the mechanisms of action of the relevant enzymes as well as the interaction with other biological processes.…”
Section: Discussionmentioning
confidence: 99%